Insulin resistance and oxidative stress in elderly women - Queiroz, Jeferson Lopes; Fraga, Alessandra Soares Ayres; Mello, Luciana Mello da Silva; Schuch, Natielen Jacques (Disciplinarum Scientia | Saúde, 2019)
The change in eating habits as a consequence of shortage of time and ingestion of processed foods, in association with a sedentary lifestyle, has increased the prevalence of obesity in all age groups of the population. This work was aimed at finding studies in the literature which correlate insulin resistance and oxidative stress in a population of elderly women. An integrative review of the literature with an exploratory approach was the methodology employed to conduct the work. Electronic data collection was performed in the PubMed database from October to November 2017. The MeSH terms used in the PubMed search builder were insulin resistance-oxidative stress-elderly women, joined by the connective and. The search resulted in 55 full-text papers, out of which eight met the criteria established for the present assessment. The study findings indicated that the body composition has a significant influence on the target audience regarding the occurrence of comorbidities, among which is the excessive abdominal fat, combined with a poor diet and inactivity, as a possible cause of Oxidative Stress. As a result, conditions such as Insulin Resistance, arterial hypertension and physiological changes are triggered. It may be concluded that the search to lower or maintain body weight, regular physical activity and proper diet can positively influence the reduction of the reactive oxygen species, obesity and Insulin Resistance. However, studies on this topic may help to understand the interaction between oxidative stress and insulin resistance.